SUSTAINABLE ECOTOURISM IMPLEMENTATION STRATEGY USING MULTIDIMENSIONAL SCALING ON THREE DESTINATIONS IN THE GAMBIA, WEST AFRICA - Sambou, Omar; Marjono, Marjono; Ciptadi, Gatot; Putra, Fadillah; Nurhabib, Asro (Indonesian Journal of Forestry Research, 2025)
This study aims to analyze the sustainability of three existing ecotourism destinations in the Gambia: (a) Bijilo Monkey Forest, (b) Maka Sutu Cultural Forest, and (c) the River Gambia National Park in the Gambia, West Africa, and postulate a sustainable policy strategy based on the outcome of the analysis through questionnaires, observations, and interviews. A mixed research method using Multidimensional Scaling (MDS) and Analytical Hierarchy Process (AHP) was employed to determine the sustainability status of ecotourism based on five dimensions: ecological/conservation, participation, education and recreation, economic, and control/legislation. The multidimensional sustainability index of the three destinations under study is 69.03%, 64.49%, and 54.94% for River Gambia National Park, Maka Sutu Cultural Forest, and the Bijilo Monkey Forest, respectively. This study concluded that all the sites under study are classified as sustainable. However, the community participation dimension needs improvement for fair and equitable distribution of natural resource wealth.